2016
DOI: 10.1002/cm.21285
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals a diverse family of kinesins essential for spermatogenesis in the fern Marsilea

Abstract: The male gametophyte of the semi-aquatic fern, Marsilea vestita, produces multiciliated spermatozoids in a rapid developmental sequence that is controlled post-transcriptionally when dry microspores are placed in water. Development can be divided into two phases, mitosis and differentiation. During the mitotic phase, a series of nine successive division cycles produce 7 sterile cells and 32 spermatids in 4.5-5 h. During the next 5-6 h, each spermatid differentiates into a corkscrew-shaped motile spermatozoid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…We used these kinesins as the base of our search because the entire kinesin family in Physcomitrella has recently been identified [ 37 ] and because Physcomitrella and Chlamydomonas are two of the more closely related ciliated species to Marsilea with an annotated kinesin family. We then verified our results by comparing them to the 56 kinesin-like transcripts that were previously identified in our transcriptome [ 38 ]. Our search identified one candidate kinesin-2 (MvKinesin-2) transcript and two candidate kinesin-9 (MvKinesin-9A and MvKinesin-9B) transcripts (Additional file 1 ).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…We used these kinesins as the base of our search because the entire kinesin family in Physcomitrella has recently been identified [ 37 ] and because Physcomitrella and Chlamydomonas are two of the more closely related ciliated species to Marsilea with an annotated kinesin family. We then verified our results by comparing them to the 56 kinesin-like transcripts that were previously identified in our transcriptome [ 38 ]. Our search identified one candidate kinesin-2 (MvKinesin-2) transcript and two candidate kinesin-9 (MvKinesin-9A and MvKinesin-9B) transcripts (Additional file 1 ).…”
Section: Resultssupporting
confidence: 55%
“…For example, comparative analyses of the kinesin family has shown that kinesin-2, kinesin-9, and the more recently identified, kinesin-‘orphan’ III (also referred to as kinesin-16) and kinesin-17, are only found in organisms that are ciliated at some point during the life cycle [ 28 , 36 ]. Members of these kinesin families can be found in ciliated plants such as Chlamydomonas , the moss Physcomitrella , and the water fern Marsilea , except kinesin-17, which is only present in Chlamydomona s [ 28 , 36 38 ]. The genome of Arabidopsis , a flowering plant that is never makes ciliated cells, contains none of these kinesins [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After spores are rehydrated, pre-mRNAs are unmasked, processed, and translated according to a precise spatiotemporal pattern. Stored transcripts include those encoding tubulins and centrins (Tsai et al, 2004), as well as proteins important for mitosis and flagella formation, such as kinesins (Tomei & Wolniak, 2016). More detailed information is available for the transcriptome of developing antheridia of M. polymorpha (Higo et al, 2016).…”
Section: Gene Expression In Male Germ Cellsmentioning
confidence: 99%
“…Investigations into representatives of other major plant lineages could address this question. The recent identification of a kinesin-4 with mitotic function in the fern Marsilea vestita certainly proposes to be a good starting point (Tomei & Wolniak 2016).…”
Section: Making Ends Meet: Overlaps In Flowering Plantsmentioning
confidence: 99%